Preschoolers Favor Their Ingroup When Resources Are Limited - Lee, Kristy Jia Jin; Esposito, Gianluca; Setoh, Peipei (Frontiers in Psychology, 2018)
The present study examined how two- to four-year-old preschoolers in Singapore (N = 202) balance fairness and ingroup loyalty in resource distribution. Specifically, we investigated whether children would enact fair distributions as defined by an equality rule, or show partiality toward their ingroup when distributing resources, and the conditions under which one distributive strategy may take precedence over the other. In Experiment 1, children distributed four different pairs of toys between two puppets. In the Group condition, one puppet was assigned to the same group as the child while the other puppet was assigned to a different group using colored stickers in a minimal group paradigm; in the No Group condition, no group assignments were made. Children’s distributions in each condition were assessed for whether the toys were fairly (equally) distributed or unfairly (unequally) distributed in favor of either puppet. Experiment 2 was identical to Experiment 1, except that a third identical toy was introduced following the distribution of each toy pair. Distributions were separately assessed for whether the first two toys were fairly (equally) distributed or unfairly (unequally) distributed in favor of either puppet, and whether children distributed the third toy to the ingroup or outgroup puppet. Overall, the vast majority of children abided by an equality rule when resources were precisely enough to be shared between recipients, but distributed favorably to the ingroup member when there was limited resource availability. We found that fairness trumped ingroup loyalty except in resource distribution involving limited resources. Our findings are consistent with findings from other resource distribution studies with preschoolers and similar studies measuring young infants’ expectations of distributive behaviors in third-party observations. Taken together, there is evidence suggesting stability in the development of knowledge to behavior in the subdomains of fairness and ingroup loyalty.